RELATIONAL DATABASE AND GRAPH DATABASE: A COMPARATIVE ANALYSIS - Medhi, Surajit; Baruah, Hemanta Kumar (Journal of process management and new technologies, 2017)
Since 1970, relational database models have been in use for storing, manipulating and retrieving data. The importance of relational databases is going to decrease due to the exponential growth of data as it is difficult to work with large number of joining tables. For such kinds of problems, one of the best solutions is to use graph database for storing data. The graph database can be used to store highly connected data. In this article, we are going to put forward a comparison between relational database and graph database with reference to an experiment performed.